Carvedilol improves left ventricular diastolic dysfunction in patients with transfusion-dependent thalassemia - Suchaya Silvilairat; Pimlak Charoenkwan; Suwit Saekho; Adisak Tantiworawit; Nipon Chattipakorn (Wolters Kluwer Medknow Publications, 2021)
Background: Iron overload cardiomyopathy is the most common cause of death in patients with transfusion-dependent thalassemia. Aim: The aim of this study was to determine the efficacy of carvedilol treatment in patients with transfusion-dependent thalassemia who had left ventricular diastolic dysfunction. Methods: Eighteen patients with transfusion-dependent thalassemia who had left ventricular diastolic dysfunction were enrolled. All patients had normal left ventricular systolic function and were given carvedilol with the target dose of 0.8 mg/kg/day. Ventricular function and the level of cardiac iron were assessed by echocardiography and magnetic resonance imaging at 0, 3, and 6 months. Results: The median age of the patients was 19 years (range 13-25 years). Four patients had severe left ventricular Grade III diastolic dysfunction and fourteen patients had Grade II diastolic dysfunction. The grade of left ventricular diastolic dysfunction was improved at 3 months after the carvedilol treatment. The Doppler parameters, including pulmonary vein atrial reversal velocity, pulmonary vein atrial reversal duration, and the difference of pulmonary vein atrial reversal and the mitral valve atrial contraction wave duration at 3 months after the carvedilol treatment, were significantly lower than these parameters before the treatment. Conclusions: Among patients with transfusion-dependent thalassemia who had left ventricular diastolic dysfunction without systolic dysfunction, treatment with carvedilol for 3 months was associated with improvement in Doppler parameters of left ventricular diastolic function. However, this finding and its clinical significance need to be confirmed in further double-blind controlled studies.